2007
DOI: 10.1111/j.1365-2761.2007.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas disease in farmed Atlantic salmon, Salmo salar L., and rainbow trout, Oncorhynchus mykiss (Walbaum), in Norway

Abstract: The present paper describes, for the first time, clinical signs and pathological findings of pancreas disease (PD) in farmed Atlantic salmon, Salmo salar L., and rainbow trout, Oncorhynchus mykiss (Walbaum), in sea water in Norway. Similarities and differences with reports of PD from Ireland and Scotland are discussed. Samples of 68 rainbow trout from disease outbreaks on 14 farms and from 155 Atlantic salmon from outbreaks on 20 farms collected from 1996 to 2004 were included in the present study. The histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 34 publications
2
83
1
Order By: Relevance
“…The salmon in 11 of these farms were moderately to strongly infected with Paranucleospora theridion, and their tissues contained low to moderate amounts of SAV. It has been thoroughly demonstrated that SAV play an important role in the development of PD (Nelson et al 1995, McLoughlin et al 1996, and high mortalities have been reported (Taksdal et al 2007, Fringuelli et al 2008. However, as several challenge experiments have shown (McLoughlin et al 1996, Desvignes et al 2002, Christie et al 2007), SAV might not be solely responsible for the PD outbreaks that occur in marine farms for salmonids.…”
Section: Pancreas Diseasementioning
confidence: 99%
“…The salmon in 11 of these farms were moderately to strongly infected with Paranucleospora theridion, and their tissues contained low to moderate amounts of SAV. It has been thoroughly demonstrated that SAV play an important role in the development of PD (Nelson et al 1995, McLoughlin et al 1996, and high mortalities have been reported (Taksdal et al 2007, Fringuelli et al 2008. However, as several challenge experiments have shown (McLoughlin et al 1996, Desvignes et al 2002, Christie et al 2007), SAV might not be solely responsible for the PD outbreaks that occur in marine farms for salmonids.…”
Section: Pancreas Diseasementioning
confidence: 99%
“…Rainbow trout host parasites, such as Gyrodactylus salaris (Peeler & Thrush, 2004), and have a high susceptibility to salmon lice (Lepeophtheirus salmonis) (Fast et al, 2002;Gjerde & Saltkjelvik, 2009). They may also carry a number of salmonid diseases (Hodneland et al, 2005;Taksdal et al, 2007;Kristoffersen et al, 2009). Farming and escapes of rainbow trout may therefore contribute to the high infestation rate of sea lice on wild salmonids (Birkeland & Jakobsen, 1997;Finstad et al, 2000;Bjørn et al, 2001;Heuch & Mo, 2001), especially when farms are sited on smolt migration routes (Krkosek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical (IHC) examination was performed essentially according to Brudeseth et al 2002 with minor modifications (Taksdal et al 2007 Virus isolation and identification. Pooled pieces of tissue from each of the sampled fish were homogenized and the samples cleared by low-speed centrifugation according to routine procedures.…”
Section: Samplingmentioning
confidence: 99%